Habilidades del desarrollador de software en la entrega a tiempo de proyectos; Software developer skills in delivering projects on time - José Luis Cantú Mata (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2024)
– The purpose of the study is to analyze the skills of software developers in delivering projects on time through the perception of 308 companies that have contracted the service in this area and are located in the Monterrey metropolitan area. A measurement instrument of 20 items was applied, using a multivariate model of structural equations using the confirmatory factor analysis technique. The data was treated with the statistical packages SPSS and AMOS, the results comply with the adjustment of the model.
Keywords: J24; L86; M11; 330; Competences; skills; software developer; time; quality